Prioritization of sub watersheds based on erosion hazard parameter’s analysis using remote sensing and GIS techniques - MISHRA, C. D.; JAISWAL, R. K.; NEMA, A. K.; CHANDOLA, V. K. (Journal of Soil and Water Conservation, 2020)
The erosion hazard parameters (EHP) which depends on morphometric parameter of watershed, sediment production rate and sediment yield analysis have been used for prioritization of sub watersheds with GIS and remote sensing techniques. Thirteen parameters namely drainage density, drainage texture, stream frequency, length of overland flow, mean bifurcation ratio, drainage intensity, circularity ratio, elongated ratio, form factor, shape factor, compactness coefficient, sediment yield and sediment production rate has been considered as erosion hazard parameters. These parameters were ranked according to their behavior for erosion. Compound value of these parameters were estimated for deciding the priority. The final priorities for soil and water conservation management work are grouped into five categories. Out of 92.32 km2 area of watershed, 17.19 km2 (18.6%) requires immediate attention or of very high priority, 26.45 km2 ( 28.65%) requires high priority, 22.81 km2 ( 24.77%) requires medium priority 11.92 km2 (12.91%) requires low priority and about 13.95 km2 (15.11%) area requires very less or no priority.